Remote Sensing of Watershed - Wang, Jingzhe; Hu, Zhongwen; Wu, Yangyi; Zhang, Jie (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on applying remote sensing techniques in watersheds in terms of hydrology, ecology, environment, and human activities. It aims to contribute to the current understanding of integrating research scopes and developing advanced methods in the field of remote sensing of watershed. The development of the multiscalar, multidimensional, and interdisciplinary nature of the application of remote sensing in watershed studies is of particular interest. Special attention is given to watershed mapping, monitoring of underlying surface elements in the watershed, inversion of water cycle parameters, water resource assessment, acquisition of watershed ecological environment parameters, monitoring natural disasters, analyzing upstream and downstream, supporting water governance priorities, water resource development, and irrigation water management. The studies propose a series of advanced data, models, and strategies to serve watershed research better.